DECENTRALIZED AND DELEGATED AFFAIRS OF A STATE ADMINISTRATION IN THE FIELD OF AGRICULTURE - Golić, Darko; Pocuca, Sara (Economics of Agriculture, 2017)
In the Republic of Serbia, the distribution of jurisdiction in the feld of agriculture has a distinctive character. Jurisdiction for the affairs in the feld of agriculture is disposed on different levels of government. This partition is followed by the different legal order of affairs, which non-central entities perform. The measure of the provincial jurisdiction is not closed in advance, but its parameters are determined by the republican jurisdiction to arrange a system and pursue a policy, leaving this level of jurisdiction to the province, which, depending on the current needs in the feld of agriculture, will be determined as issues of provincial interest. These measures necessarily include a normative, planned, organisational, financial and administrative aspect. In regard to delegated affairs, it is mainly about the classical administrative activities of authoritative character, provided that the supervisory powers are much greater. The objective of this paper is to identify original and delegated affairs of a state administration, their content and the relation between the state administrative authorities and the administrative authorities of decentralized units in their performing.